Deposition effect of inhaled particles in the human: Accurate health risks of personal exposure to PAHs and their derivatives from residential solid fuel combustion. (1st February 2023) - Feng, Rong; Xu, Hongmei; Gu, Yunxuan; Gao, Min; Bai, Yunlong; Liu, Meixuan; Shen, Zhenxing; Sun, Jian; Qu, Linli; Hang Ho, Steven Sai; Cao, Junji
Abstract: The drastic household clean heating renovation has been undertaken in rural northern China since 2017. A method incorporating the deposition efficiency of particulate matters (PMs) in the human respiratory tract is firstly introduced into the personal exposure (PE) study which is more accurately assess the health risks of homemakers inhaling PM-bound four subclasses polycyclic aromatic hydrocarbons (PAHs) emitted from different solid fuels (i.e., biomass, raw coal chunk, and clean coal). Homemakers using clean coal show the lowest exposure levels of all PAH subclasses (parent, alkylated, oxygenated, and nitro PAHs) and total quantified PAHs (ΣPAHs). Remarkable reductions of 93.9% and 89.0% on ΣPAHs in PE PM2.5 are observed with the substitutions of the raw coal chunk and biomass fuel by the clean coal, respectively. 86.8–96.8% of ΣPAHs are inhaled by the human body, while approximately 22.4–44.8% are deposited in the respiratory tract. The deposition concentrations (DC) of ΣPAHs in the biomass and raw coal chunk groups are 12 and 5 times the clean coal group, respectively. PAHs in coarse mode PE particles with an aerodynamic size between 2.5 and 100 μm mostly deposit in the head airway (HA) (98%). Moreover, the PAHs in fine particles (i.e., with aerodynamic size less than 2.5 μm) mainly deposit in the alveolar region (AR), accounting for 20–70% of ΣPAHs. Replacing biomass and raw coal chunk with clean coal reduced incremental lifetime cancer risks (ILCR) by 91% and 92%, respectively. This study improves the understanding of the PM-bound PAHs deposition in the human respiratory system and contributes to the promotion of domestic energy transition in rural northern China. Graphical abstract: Image 1 Highlights: Respiratory deposition and health effect of size-resolved PM PAHs are evaluated. 98% PM > 2.5 was deposited in head airway, while 20–70% PM2.5 deposited in alveolar. Clean coal substitution reduces PAHs exposure and associated cancer risk by ∼90%. Cancer risk assessment based on respiratory deposition efficiency is more accurate.